The relationship between water‐holding capacities of soybean–whey mixed protein and ice crystal size for ice cream. (3rd May 2021) - Liu, Yayong; Liu, Aiguo; Liu, Lizeng; Kan, Zhuorui; Wang, Weijia
Abstract: This study investigated the water‐holding properties of a mixture of whey protein (WP) and soy protein (SP) (WP–SP) and their effect on ice crystal size using low‐field nuclear magnetic resonance (LF‐NMR) and freezing microscopy techniques. The size of ice crystals determines the perceived quality of ice cream. Furthermore, the addition of plant protein facilitates the study of the water‐holding properties of mixed proteins and limits the size of ice crystals. WP and SP proteins were mixed in different ratios (10:0–0:10), the water‐holding capacity was measured by LF‐NMR, and the size of the ice crystals observed by freezing microscopy. The results showed that the water‐holding capacity of the mixed proteins increased with increasing SP content. A mixed protein ratio of 3:7 had the highest water‐holding capacity but also displayed a strong inhibitory effect on the size of the ice crystals formed. Hence, the ice crystal area of SP solution alone was 128.96 μm 2 with an average diameter of 11.74 μm, and, in contrast, a mixed protein ratio of 3:7 had an ice crystal area of 79.49 μm 2, and an average diameter of 8.61 μm. Practical Applications: The study provides insight into the design of an ice cream formula to assist with the industrial production of ice cream products of improved quality and consumer appeal. Abstract : Water holding properties and effects on ice crystal size in ice cream were investigated by using low field nuclear magnetic resonance and freezing microscopy techniques. The highest water‐holding capacities and a strong inhibitory effect on the size of the ice crystals is at whey protein and soy protein mixed in ratio of 3:7.